Aplikasi Adsorben Nanopartikel Magnetit (Fe3O4) untuk Penyisihan Metilen Biru dari Ferric Nitrate Nonahydrate dengan Metode Sol-Gel - Mauli Faulina; Ratna Sari; Nahar Nahar (Politeknik Negeri Lhokseumawe, 2023)
The application of magnetite (Fe3O4) nanoparticle adsorbent for the removal of methylene blue from ferric nitrate nonahydrate by sol-gel method. This study was conducted to determine the effect of variations in calcination temperature and stirring time on density, and adsorption power of magnetite (Fe3O4) nanoparticles on methylene blue with variations in stirring time of 2 hours; 3 hours; 4 hours; 5 hours, and 6 hours, as well as variations in calcination temperature of 200°C; 250°C; 300°C; 350°C and 400°C. Characterization of magnetite (Fe3O4) nanoparticles was carried out using XRD, and SEM instruments. Methylene blue concentration after adsorption was measured using Uv-Vis Spectrophotometer. Determination of adsorbent surface area was done by iodine absorption test. The results showed a decrease in density along with the increase in calcination temperature and the longer the stirring, the density value will increase. Magnetite (Fe3O4) nanoparticles effectively increase the adsorption capacity of methylene blue, with the best results at a stirring time of 6 hours and a calcination temperature of 400°C the concentration after adsorption drops to 1.7316 ppm. The best iodine adsorption capacity is found in the sample of 6 hours stirring time and 200°C calcination temperature, which is 1027.89 mg/gr. The crystal size obtained based on calculations from the Scherrer equation at a variation of 3 hours stirring time and 200°C calcination temperature is 0.2 nm and the surface morphological structure of magnetite (Fe3O4) nanoparticles at the same stirring time and calcination temperature looks clustered with sizes ranging from 0.4 nm to 0.9 nm.